P246 Neglected keratitis caused by Exserohilum rostratum from the arid region of north-west India leading to vision loss—a case report. (20th September 2022) - Netar, Suresh; Choudhary, Meenu; Verma, Pushpanjali; Rastogi, Vijyalatha; Gupta, Mansi
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objectives: To report a case of complete loss of vision due to delay in diagnosis of fungal keratitis caused by Exserohilum rostratum in an immunocompetent patient from the arid area of north-west India. Method: A 65-year-old female farmer was admitted to ophthalmology with a history of pain, redness, watering, and foreign body sensation in the left eye for 2 months. She had a history of trauma by splinters 2 months back. On ocular examination, a large corneal ulcer of about 7 × 8 mm size at 2-8'o' clock position in the left eye was present with diffuse corneal edema. She had no history of diabetes mellitus, hypertension, tuberculosis, COVID-19, and steroid eye drops instillation. There was no relevant previous history of any ocular surgery also. She was negative for hepatitis-B and human immune deficiency virus on serology. All her hematological parameters were within normal limits. Patient was treated with moxifloxacin, carboxy methyl cellulose eye drops, and Neosporin eye ointment for around 2 months at primary health care facilities and later referred to our hospital for further management. Corneal scraping of the patient was sent to our laboratory for potassium hydroxide mount and culture identification. Results: Fungus was identified as E. rostratum on the basis of gross, macroscopic, and microscopic morphology. Gram's staining was bacteriologically negative while true fungal hyphae were seen. In KOH mount pigmented, septate, and branched true hyphae were seen. Bacterial culture was reported sterile. Lactophenol cotton blue mount of culture revealed dematiaceous hyphae along with 4-9 septate elongated, ellipsoid macroconidia of 14-90  μ m with prominent dark conspicuous hilum and geniculate conidiophore arranged sympodially. On the basis of these characteristics, it was diagnosed as E. rostratum . After the diagnosis patient was switched over to topical natamycin 5% two hourly and oral itraconazole 200 mg BD from moxifloxacin and neosporin. To which the patient responded symptomatically. Ulcer healed in a month leaving behind a lateral scar. However, vision is permanently compromised and the patient is advised for therapeutic penetrating keratoplasty (TPK). Conclusion: Exserohilum rostratum is generally regarded as a pathogen in hot and humid climates. However, the isolation of this organism in our area highlights the pathogenic potential of this emerging fungus in arid climates also. Ophthalmologists need to be made aware of the significance of prompt mycological identification to prevent vision loss.